Kinetic Determination of Paracetamol using a Novel Belousov-Zhabotinskii Oscillating System Catalyzed by a Tetraazamacrocyclic Complex - Gang Hu; Qin Wang; Min Meng; Ming Ying Lu; Fu Sheng Zhao; Lin Hu (E-Journal of Chemistry, 2012)
A new analytical method for determination of paracetamol is proposed. This method is based on a novel B-Z oscillating system, which involves a Tetraazamacrocyclic Complex [CuL](ClO4)2 as catalyst and malic acid as the substrate. The ligand L in the complex is 5,7,7,12,14,14-hexamethyl-1,4,8,11-tetraazacyclotetradeca-4,11-diene. By perturbation mount of paracetamol on the B-Z system, there is a linear relationship between the changes in the oscillation amplitude and the logarithm of paracetamol concentration in the range 5×10-7 to 2×10-4 M, with a correlation coefficient of 0.99743. The effects of influential variables, such as the concentration of reaction components, temperature and on the determinations were studied. The probable mechanism involving the perturbation of paracetamol on the oscillating chemical system was also discussed.